Digitalization, Planning, and Sustainability in Project Management in Jordan’s Construction Sector: Enhancing Project Success through Stakeholder Engagement and Virtual Work Dynamics - Alkhatatneh, Omar A.; Li, Wu; Cheng, Yao; Frah, Mohamed A.; Dao, Daojun; Almajali, Ibrahim Omar Ibrahim (European Journal of Applied Sciences, 2025)
Due to the growing client requirements for cost-effective solutions and environmentally friendly projects, the construction business remains pressured to deliver sustainable project results and objectives. Although the role of sustainability in project management has been widely explored and documented, there is growing research interest regarding integrating digitalized tools and sustainable project planning into sustainable project success; its relation to virtual teams is explicitly relatively unknown, especially within the developing world context such as Jordan. This research is intended to fill this gap by assessing the effect of sustainability in project management, Digitalization, and sustainable project planning on sustainable project success, with the virtue of the work environment acting as a moderator and stakeholder engagement as a mediator. To meet this research aim, the structured questionnaire was distributed to one hundred project engineers, managers, and other project professionals in Jordan’s construction industry. The gathered data were investigated to evaluate the claimed link using the Partial Least Squares (PLS) approach using the Smart PLS tool. The findings show that the success of a project mainly depends on digitization, environmentally friendly project design, and sustainable project management. Moreover, the virtual work environment and stakeholder engagement were recognized as the significant mediator and moderator of these relationships. The implications drawn from the study point to the critical need for construction firms to embrace integrated and sustainable project management models, incorporate technology in their execution, and be keen to involve stakeholders. Therefore, these concepts might be used to raise project-level organizational performance and help to meet more general sustainable development targets in the building sector.